Vocal music enhances memory and language recovery after stroke: pooled results from two RCTs. Issue 11 (6th October 2020) - Sihvonen, Aleksi J.; Leo, Vera; Ripollés, Pablo; Lehtovaara, Terhi; Ylönen, Aki; Rajanaro, Pekka; Laitinen, Sari; Forsblom, Anita; Saunavaara, Jani; Autti, Taina; Laine, Matti; Rodríguez‐Fornells, Antoni; et al.
Abstract: Objective: Previous studies suggest that daily music listening can aid stroke recovery, but little is known about the stimulus‐dependent and neural mechanisms driving this effect. Building on neuroimaging evidence that vocal music engages extensive and bilateral networks in the brain, we sought to determine if it would be more effective for enhancing cognitive and language recovery and neuroplasticity than instrumental music or speech after stroke. Methods: Using data pooled from two single‐blind randomized controlled trials in stroke patients ( N  = 83), we compared the effects of daily listening to self‐selected vocal music, instrumental music, and audiobooks during the first 3 poststroke months. Outcome measures comprised neuropsychological tests of verbal memory (primary outcome), language, and attention and a mood questionnaire performed at acute, 3‐month, and 6‐month stages and structural and functional MRI at acute and 6‐month stages. Results: Listening to vocal music enhanced verbal memory recovery more than instrumental music or audiobooks and language recovery more than audiobooks, especially in aphasic patients. Voxel‐based morphometry and resting‐state and task‐based fMRI results showed that vocal music listening selectively increased gray matter volume in left temporal areas and functional connectivity in the default mode network. Interpretation: Vocal music listening is an effective and easily applicable tool to support cognitive recovery after stroke as well as to enhance early language recovery in aphasia. The rehabilitative effects of vocal music are driven by both structural and functional plasticity changes in temporoparietal networks crucial for emotional processing, language, and memory.